1998
DOI: 10.1097/00006534-199801000-00024
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Hemodynamics in Jejunal Flaps of Rabbits due to Ischemia, Venous Congestion, and Reperfusion as Measured by Means of Colored Microspheres

Abstract: The effect on the jejunal hemodynamics of restoration of blood flow of the jejunal artery or vein in the free jejunal flap has not yet been elucidated. In the present study, a model of ischemia and reperfusion in the jejunal flap of rabbits, and that of venous congestion and reperfusion, were prepared. Jejunal blood flow was measured by means of colored microspheres, and changes in jejunal blood flow were analyzed. Three segmental jejunal flaps were designed on each rabbit (n = 16), with one artery and one vei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
8
0
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 6 publications
5
8
0
1
Order By: Relevance
“…Restoring arterial inflow within 3 hours could usually achieve a successful salvage and a patent esophagus; however, relieving venous congestion that occurs for more than 30 minutes resulted in persistent and prolonged congestion of the flap and, often, late complications. These observations are parallel to those of Tsuchida and colleagues, 15 which revealed that a longer period of time is required to recover normal blood inflow after releasing the venous occlusion. Venous congestion for only 5 minutes induces hemorrhage in the lamina propria of the jejunum, and venous congestion lasting more than 30 minutes leads to an irreversible change in the entire jejunal wall.…”
Section: Discussionsupporting
confidence: 85%
“…Restoring arterial inflow within 3 hours could usually achieve a successful salvage and a patent esophagus; however, relieving venous congestion that occurs for more than 30 minutes resulted in persistent and prolonged congestion of the flap and, often, late complications. These observations are parallel to those of Tsuchida and colleagues, 15 which revealed that a longer period of time is required to recover normal blood inflow after releasing the venous occlusion. Venous congestion for only 5 minutes induces hemorrhage in the lamina propria of the jejunum, and venous congestion lasting more than 30 minutes leads to an irreversible change in the entire jejunal wall.…”
Section: Discussionsupporting
confidence: 85%
“…Jejunal lamina propria haemorrhage commences 5 minutes following venous congestion, moreover irreversible tissue injury is evident at 30 minutes. 13,14 The challenge becomes greater in the situations where the EJV and IJV are unavailable. Insufficient venous drainage through the smaller neck veins would cause venous engorgement hence enhancing vessel size discrepancy and the risk of failure.…”
Section: Discussionmentioning
confidence: 99%
“…Venous outflow blockage (congestion) leads to interstitial edema, venous wall injury, extravascular bleeding, and hemorrhagic necrosis [3,4]. In addition, venous thrombi caused by congestion may induce vasospasm, which prolongs anoxia after reperfusion and exaggerates the injury.…”
Section: Discussionmentioning
confidence: 99%
“…However, tissue integrity and cellular function after venous congestion were shown to be poorer than arterial ischemia in segmental rat small bowel [3]. Also, venous congestion has been a greater concern than arterial ischemia in the viability of vascularized tissue flaps [4]. We tested the hypothesis that during hepatic vascular isolation, abdominal visceral ischemia rather than venous congestion may have beneficial effect on reperfusion injury and survival outcomes.…”
Section: Introductionmentioning
confidence: 99%